2015
DOI: 10.1177/0269094215601958
|View full text |Cite
|
Sign up to set email alerts
|

Regional poverty mapping in Europe – Challenges, advances, benefits and limitations

Abstract: The 'at-risk-of-poverty' rate is the most widely recognised indicator of income poverty. Its principal advantage is that it is relatively straightforward to define and (given appropriate data) to calculate. National at-risk-of-poverty rates play a key role in monitoring EU2020 objectives relating to combating poverty. Regional patterns of poverty have the potential to deepen our understanding of processes of impoverishment and differentiation, and how they can be more effectively addressed by policy. Estimatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…A descriptive study of Bertolini et al (2008) on rural poverty in Europe demonstrated the diversity of rural-urban disparities in individual European countries and shed light on the different drivers of rural poverty in Europe. Shucksmith et al (2009), as well as Bock et al (2015) and Weziak Bielowolska (2016) used a cross-nationally comparative dataset showing that increased rural poverty levels and a rural-urban poverty gap can be found particularly in the poorer, eastern and southern European countries, a conclusion also confirmed in detailed analysis of Eurostat data across the EU-28 by Copus et al (2015b). The coarse spatial scale of harmonised cross-national data, typically only available at the NUTS 2 regional level with the OECD Sociologia Ruralis, Vol 59, Number 3, July 2019 rural-urban identifier, and the narrow range of variables available were commented on in this study as barriers to cross-national and multidimensional research on rural poverty and social exclusion.…”
Section: Introductionmentioning
confidence: 76%
“…A descriptive study of Bertolini et al (2008) on rural poverty in Europe demonstrated the diversity of rural-urban disparities in individual European countries and shed light on the different drivers of rural poverty in Europe. Shucksmith et al (2009), as well as Bock et al (2015) and Weziak Bielowolska (2016) used a cross-nationally comparative dataset showing that increased rural poverty levels and a rural-urban poverty gap can be found particularly in the poorer, eastern and southern European countries, a conclusion also confirmed in detailed analysis of Eurostat data across the EU-28 by Copus et al (2015b). The coarse spatial scale of harmonised cross-national data, typically only available at the NUTS 2 regional level with the OECD Sociologia Ruralis, Vol 59, Number 3, July 2019 rural-urban identifier, and the narrow range of variables available were commented on in this study as barriers to cross-national and multidimensional research on rural poverty and social exclusion.…”
Section: Introductionmentioning
confidence: 76%
“…Concerning the measurement of poverty, Bodea and Herman (2014) state, on the basis of preceding research, that poverty can be measured through the help of the following indicators: poverty headcount ratio, rate of poverty, Gini coefficient and other indicators that concern living aspects such as the access to water, durable goods ownership, education and spending undertaken for consumption purposes. Oppositely, Copus et al (2015) affirm that another measure of quantifying poverty is the at-risk-of-poverty rate, used by the European Union when establishing the efficiency of poverty reduction goals specified in the EU 2020 strategy. More precisely, the at-risk-of-poverty rate displays the percentage of individuals who belong to households in which the available income is under the threshold of 60% computed with reference to the national median.…”
Section: Poverty and Social Exclusionmentioning
confidence: 99%
“…For instance, Bertolini et al (2008) stress the urban-rural divides in terms of socioeconomic performances. In particular, rural areas have suffered from socioeconomic weakness and negative demographic trends since the mass urbanization process (Copus et al, 2015), which today make them more vulnerable also to adverse natural events. The National Strategy for Inner Areas has also assessed this issue (Barca et al, 2014).…”
Section: Term Of Reference On Vulnerability and Risks And Place-basementioning
confidence: 99%